2016
DOI: 10.1039/c5ay01404b
|View full text |Cite
|
Sign up to set email alerts
|

UPLC-QTOF-MS based metabolomics coupled with the diagnostic ion exploration strategy for rapidly evaluating sulfur-fumigation caused holistic quality variation in medicinal herbs, Moutan Cortex as an example

Abstract: A novel LC-MS based metabolomics strategy for holistic quality evaluation of sulfur-fumigated herb.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 38 publications
(36 reference statements)
0
13
0
Order By: Relevance
“…To monitor the sulfur-fumigation process of AB and dissect the chemical transformation mechanisms of the screened markers, five major active AB compounds (EC, BE, OA, FA, and 5-HF) were simultaneously determined at seven time points within 24 h, as well as four weight ratios of sulfur to herbal materials (blank, 1:20, 1:40, and 1:80) (Supplementary Table S3 ). Furthermore, PCA and PLS-DA analysis with SIMCA software were used to further evaluate the extent of the sulfur-fumigation ( Figure 5 ) ( Li et al, 2016 ; Kang et al, 2017 ). Overall, the quality of AB was significantly different before and after sulfur-fumigation.…”
Section: Resultsmentioning
confidence: 99%
“…To monitor the sulfur-fumigation process of AB and dissect the chemical transformation mechanisms of the screened markers, five major active AB compounds (EC, BE, OA, FA, and 5-HF) were simultaneously determined at seven time points within 24 h, as well as four weight ratios of sulfur to herbal materials (blank, 1:20, 1:40, and 1:80) (Supplementary Table S3 ). Furthermore, PCA and PLS-DA analysis with SIMCA software were used to further evaluate the extent of the sulfur-fumigation ( Figure 5 ) ( Li et al, 2016 ; Kang et al, 2017 ). Overall, the quality of AB was significantly different before and after sulfur-fumigation.…”
Section: Resultsmentioning
confidence: 99%
“…LC-MS based metabolomics approaches are being successfully employed in many evaluations of the holistic quality of medicinal herbs. UPLC-QTOF-MS based metabolomics coupled with characteristic ion exploration, a novel and practical strategy was proposed for the rapid evaluation of holistic quality variations caused by the sulfur-fumigation of CM [ 137 ]. The results suggested that sulfur-fumigation could significantly affect the holistic quality of CM by chemically transforming pinane monoterpene glucosides, the main bioactive components of CM, to their corresponding sulfonate derivatives.…”
Section: Analytical Methods For Quality Evaluation Of CMmentioning
confidence: 99%
“…Monoterpene glycosides. The structural characteristics included the possession of the "cage-like" pinane skeleton, with different substituent groups, typically glucosyl and phenyl-containing groups [21]. In addition, one feature of the fragmentation in MS/MS was distinctive for the monoterpene glycoside.…”
Section: Qualitative Analysismentioning
confidence: 99%
“…It is notable to highlight that all the 34 phenolic compounds were reported for the first time in tree and herbaceous peony seed oils. The monoterpene glycosides and paeonol derivatives, called "Paeonia glycosides", as a group reported widely as the main bioactive components in Moutan Cortex and other herbal medicines from Paeonia plants [21], have not been reported in other vegetable oils yet.…”
Section: Qualitative Analysismentioning
confidence: 99%